International Health in the Light of National Health Act in Nigeria: The Critical Issues - Brian O., Ogbonna; Samuel U., Uzodinma; Ogechukwu L. , Okwuosa (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2016)
Treaties and rapid developments in science integrate nations, and advances in technology havereduced the world into a global village. With an estimated seven billion global populationcoupled with high human traffic and movement of goods and services across borders, nationshave been at increased risk of disease outbreak and epidemics across borders which necessitatedfor disease surveillance, prevention, management and control through corporation between nations at the borders. With the introduction of the national health act in Nigeria in 2014, thefederal ministry of health was charged with the responsibility of ensuring and promoting theprovision of Quarantine and Port Health Services. This article assessed the fundamental issues insuccessful port health services.